A NEEDS ANALYSIS OF PROJECT-BASED INTERACTIVE MULTIMEDIA FOR ENHANCING SPATIAL ABILITY IN ELEMENTARY SCHOOL STUDENTS - Reni Setyaningsih; Wiryanto Wiryanto; Rini Setianingsih (Prima: Jurnal Pendidikan Matematika, 2026)
This study aims to analyze the needs for interactive multimedia based on Project-Based Learning (PjBL) in elementary schools. It was conducted in ten schools in Mojowarno sub-district, Jombang Cistrict, involving 227 fifth-grade students and 10 teachers. Data were collected using questionnaires consisting of 10 items for students and teachers, rated on a 5-point Likert scale. This research is motivated by the fact that students’ spatial abilities remain low, as reflected in the 2024 ANBK geometry scores, which were the lowest at 50.14. It underscores the need for effective learning media in mathematics instruction. The results of the questionnaire show the majority of students require digital learning media to facilitate understanding of lesson material (98.67%) and prefer media that integrate images, videos, animations, and games (86.34%). Both students and teachers expressed a need for interactive multimedia based on PjBL to support mathematics learning. The results of the questionnaire show that all teachers agreed on the importance of media that help students visualize abstract concepts (40% strongly agreed; 60% agreed) and media that are easy to use anytime and anywhere (60% strongly agreed; 40% agreed). These findings highlight the importance of developing interactive multimedia based on PjBL to enhance fifth-grade students’ spatial abilities and improve learning outcomes in mathematics.